Seasonal patterns and responses to an extreme climate event of rotifers community in a shallow eutrophic Pampean lake - Diovisalvi, Nadia Rosalia (2015)
Shallow lakes of temperate areas experience seasonal and inter-annual variability in weather conditions, impacting on their biological communities. Here, we studied the temporal fluctuation of the zooplankton community in a highly eutrophic shallow lake, Laguna Chascomús. Rotifers and the cyclopoid copepod Acanthocyclops robustus dominated the community. The most important rotifers were Brachionus caudatus, B. havanaensis, and Keratella tropica. The abundance of the two Brachionus species reached maximum values in late summer/early autumn. In contrast, K. tropica and A. robustus did not display seasonal patterns. A prolonged period of low water temperature resulted in a massive fish winterkill event (in 2007), which seemingly allowed the development of unusually dense populations of cladocerans. We used vector autoregressive models to analyze the rotifer time series. The model accounted for 76% of the variance in rotifer abundance and provided evidence of their dependence on temperature and chlorophyll a. In addition, the impact of the fish winterkill on rotifer abundance could be assessed through intervention analysis. The evidence collected here suggests that the zooplankton community structure is controlled by fish planktivory, while rotifers population dynamics are mostly driven by temperature and available food. Both processes seem highly responsive to forcing weather variables.